A Comparative Analysis between Intrinsic and Extrinsic Drivers of Inflation - Habanabakize, Thomas; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2024)
In most economies, particularly in developing countries, addressing inflation remains a significant macroeconomic challenge. This study seeks to examine the factors, both internal and external, that contribute to inflationary trends in South Africa. To achieve this objective, the authors employ the Johansen cointegration test, vector error correction approach, impulse response function, and variance decomposition on quarterly time series data spanning from 1994 to 2022. The findings of the study provide compelling evidence suggesting that both internal and external factors play a statistically significant role in influencing inflation. However, external forces exert a greater impact on the inflationary pressures witnessed in South Africa when compared to internal factors. Notably, factors such as trade openness, exchange rates, and imported prices contribute significantly to the elevated inflation rate in South Africa. On the other hand, internal factors like sustainable government expenditure, interest rates, and net export prices prove effective in mitigating the inflation rate.